2022
DOI: 10.3390/jcm11030816
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Small Extracellular Vesicles May Contribute to Vaso-Occlusive Crises in Sickle Cell Disease

Abstract: We previously found that the plasma of patients with sickle cell disease (SCD) contains large numbers of small extracellular vesicles (EVs) and that the EVs disrupt the integrity of endothelial cell monolayers (especially if obtained during episodes of acute chest syndrome, ACS). The present study was designed to test the generality of this finding to other complications of SCD, specifically to evaluate the possibility that circulating EVs isolated during a vaso-occlusive crises (VOC) also cause damage to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This group showed that SCD exosomes cause endothelial monolayer disruption [ 144 , 145 , 161 ]. Importantly, the extent of the endothelial disruption was even greater using exosomes circulating during acute chest syndrome [ 161 ] or during VOC [ 162 ], compared to exosomes purified from the plasma of patients at steady state.…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%
“…This group showed that SCD exosomes cause endothelial monolayer disruption [ 144 , 145 , 161 ]. Importantly, the extent of the endothelial disruption was even greater using exosomes circulating during acute chest syndrome [ 161 ] or during VOC [ 162 ], compared to exosomes purified from the plasma of patients at steady state.…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%